Assessment of Integrative Learning in Music Therapy - Rylund, Katie; Zaldarriaga, Iansa (My University, 2010)
This project examined whether or not students used content from designated music therapy courses outside their classroom work. Documentation of when and how the content was used was examined. Sustainability of the use of content outside the courses was noted, along with an examination of any perspectives changes that students experienced.
Color poster with text, images, and graphs.
Keywords: Music therapy; Learning, Psychology of; Life skills; Posters